And on that farm he had a wife : Ontario farm women and feminism, 1900-1970 - Halpern, Monda M., 1963- (McGill-Queen's University Press, 2001)
Annotation Focusing on white; Anglo-Protestant farm women in southern and southwestern Ontario, Monda Halpern argues that many Ontario farm women were indeed feminist, and that this feminism was more progressive than their conservative image has suggested. In And On That Farm He Had a Wife Halpern demonstrates that Ontario farm women adhered to social feminism -- a feminism that focused on values and experiences associated with women and that emphasized the differences between women and men, promoting female specificity, solidarity, and separatism. These principles were informed by farm women's overlapping roles as wives and unpaid farm labourers. Because men typically owned the "family farm", farm women's economic welfare depended largely on the smooth negotiation of their interconnected roles. Yet the women Halpern uncovers were surprisingly outspoken about their devaluation on the farm and about patriarchal traditions and institutions that mistreated women generally. And On That Farm He Had a Wife shows how Ontario farm wives and daughters sought to improve their lives, chiefly through the home economics movement and Women's Institutes. They committed themselves to personal development, to elevating the nature and status of their work, and to public participation in social reform designed to help others as well as themselves. All of these efforts were an expression of their social feminism, which endured even with the dramatic changes in rural life at mid-century. And On That Farm He Had a Wife will appeal to scholars and students of Canadian history, women's history, and rural studies, as well as to general readers interested in a neglected story of Ontario's past